Extractives Companies' Social Media Portrayals of Their Funding of Sport for Development in Indigenous Communities in Canada and Australia. (December 2022) - Latino, Steven; Giles, Audrey R.; Rynne, Steven; Hayhurst, Lyndsay
The extractives industry (mining, quarrying, oil, and gas) engages in corporate social responsibility (CSR) activities to reinforce its organizational legitimacy and enhance its public image. One such approach to CSR that is popular in the industry is through funding sport initiatives aimed at improving the lives of Indigenous peoples, known as sport for development (SFD). Through the adoption of a settler colonial studies lens, and using netnographic methods and discourse analysis, we examined how three extractives companies portray their funding of SFD in Indigenous communities in Canada and Australia on social media, and the ways in which it contributes to settler colonialism. We determined that there are two main discourses that extractive companies use: i) Extractives companies "help" and "partner" with Indigenous communities to enable Indigenous youth's access to the transformative power of sport; ii) longevity is strategically associated with such "help" and "partnership." The production of these discourses enables extractives companies to downplay their contributions to settler colonialism through land denigration and colonial authority.